Gender Perspective on Strengthening Graduate Contributions to Sustainable Farming Universitas Malikussaleh - Jullimursyida Jullimursyida; Khalsiah Khalsiah; Deasy Siska; Rozanna Dewi; Mawardati Mawardati; Yulia Yulia (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Women have achievements and changes in the business sector, including maintaining sustainable food security. On the other hand, the frequent absence of female farmers from agricultural development programs reflects the injustice and inequality in Indonesia between males and females. Performing daily the entire farming process, from seed preparation to planting and maintenance, and even harvesting.  Collaboration is the vehicle for improving women's skills and participation in the agricultural sector. Women farmers' roles and contributions in the coffee farming sector must be considered. The research aims: (1) to strengthening graduates in the sustainable agriculture sector at Malikussaleh University (2) to Graduates' contribution to improving women's skills to study farming for the private sector coffee agricultural and technology at Malikussaleh University. This study used the qualitative method—descriptive data in written or oral words from people and observed behavior. The results showed that one of the reasons low participation of women in cooperatives is limited land ownership had caused woman farmers not eligible to register as cooperative members. Only one person is counted from each household/family and represented by the father/husband. This research provides recommendations on improving women's role and contribution in the agricultural sector by improving their participation in the coffee sector.